2019
DOI: 10.1016/j.jtcvs.2019.02.134
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver variability impairs radiologic grading of primary graft dysfunction after lung transplantation

Abstract: Objectives: The current score for primary graft dysfunction after lung transplantation relies heavily on chest radiographs, and radiologic judgment can make the difference between the lowest (primary graft dysfunction 0) and the highest (primary graft dysfunction 3) grade. This study aimed to evaluate interobserver variability of the scoring of postoperative chest radiographs and its impact on primary graft dysfunction grades in a large single-center cohort.Methods: We retrospectively analyzed 497 lung transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Of these, PAH, female recipient, high mPAP, and oversized lung allograft have also been shown to be risk factors for PGD. 9,10 In our univariate model, female gender increases the risk for prolonged ICU LOS significantly (OR 2.27).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Of these, PAH, female recipient, high mPAP, and oversized lung allograft have also been shown to be risk factors for PGD. 9,10 In our univariate model, female gender increases the risk for prolonged ICU LOS significantly (OR 2.27).…”
Section: Discussionmentioning
confidence: 79%
“…This is consistent with findings in other studies, where the effect of gender disappears when correcting for other variables. 10 This suggests that the risk is primarily caused by other factors, such as lung size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with an increased body mass index and those with size-reduced transplants were associated with higher rates of interobserver variability. Schwarz and colleagues 3 conclude that substantial interobserver variability underlines the difficulty to grade posttransplant organ function adequately.…”
mentioning
confidence: 99%
“…We have previously shown that even trained thoracic radiologists only moderately agree in defining bilateral infiltrations in the modern era of lung transplantation, especially if radiographic changes are subtle. 5 In case of a PO 2 less than 200 mm Hg, a chest x-ray diagnosis can make a difference between PGD grade 0 and PGD grade 3. We and others believe that alternative measurements-such as the ratio of PO 2 to inspired oxygen fraction, compliance, length of mechanical ventilation or best forced expiratory volume in 1 second-might be more useful as markers of lung quality and need to be provided in future studies evaluating the effects of organ preservation strategies on primary organ function.…”
mentioning
confidence: 99%